Fuzzy approximation of an additive functional equation - G. Zamani Eskandani; Ali Reza Zamani; H. Vaezi (Journal of Function Spaces and Applications)
In this paper, we investigate the generalized Hyers– Ulam– Rassias stability of the functional equation ∑i=1mf(mxi+∑j=1, j≠imxj)+f(∑i=1mxi)=2f(∑i=1mmxi) in fuzzy Banach spaces and some applications of our results in the stability of above mapping from a normed space to a Banach space will be exhibited.